Numbers of presynaptic Ca2+ channel clusters match those of functionally defined vesicular docking sites in single central synapses - Miki, Takafumi; Kaufmann, Walter A; Malagon, Gerardo; Gomez, Laura; Tabuchi, Katsuhiko; Watanabe, Masahiko; Shigemoto, Ryuichi; Marty, Alain (Proceedings of the National Academy of Sciences - PNAS, 2017)
Many central synapses contain a single presynaptic active zone and a single postsynaptic density. Vesicular release statistics at such "simple synapses" indicate that they contain a small complement of docking sites where vesicles repetitively dock and fuse. In this work, we investigate functional and morphological aspects of docking sites at simple synapses made between cerebellar parallel fibers and molecular layer interneurons. Using immunogold labeling of SDS-treated freeze-fracture replicas, we find that Cav2.1 channels form several clusters per active zone with about nine channels per cluster. The mean value and range of intersynaptic variation are similar for Cav2.1 cluster numbers and for functional estimates of docking-site numbers obtained from the maximum numbers of released vesicles per action potential. Both numbers grow in relation with synaptic size and decrease by a similar extent with age between 2 wk and 4 wk postnatal. Thus, the mean docking-site numbers were 3.15 at 2 wk (range: 1-10) and 2.03 at 4 wk (range: 1-4), whereas the mean numbers of Cav2.1 clusters were 2.84 at 2 wk (range: 1-8) and 2.37 at 4 wk (range: 1-5). These changes were accompanied by decreases of miniature current amplitude (from 93 pA to 56 pA), active-zone surface area (from 0.0427 μm2 to 0.0234 μm2), and initial success rate (from 0.609 to 0.353), indicating a tightening of synaptic transmission with development. Altogether, these results suggest a close correspondence between the number of functionally defined vesicular docking sites and that of clusters of voltage-gated calcium channels.Many central synapses contain a single presynaptic active zone and a single postsynaptic density. Vesicular release statistics at such "simple synapses" indicate that they contain a small complement of docking sites where vesicles repetitively dock and fuse. In this work, we investigate functional and morphological aspects of docking sites at simple synapses made between cerebellar parallel fibers and molecular layer interneurons. Using immunogold labeling of SDS-treated freeze-fracture replicas, we find that Cav2.1 channels form several clusters per active zone with about nine channels per cluster. The mean value and range of intersynaptic variation are similar for Cav2.1 cluster numbers and for functional estimates of docking-site numbers obtained from the maximum numbers of released vesicles per action potential. Both numbers grow in relation with synaptic size and decrease by a similar extent with age between 2 wk and 4 wk postnatal. Thus, the mean docking-site numbers were 3.15 at 2 wk (range: 1-10) and 2.03 at 4 wk (range: 1-4), whereas the mean numbers of Cav2.1 clusters were 2.84 at 2 wk (range: 1-8) and 2.37 at 4 wk (range: 1-5). These changes were accompanied by decreases of miniature current amplitude (from 93 pA to 56 pA), active-zone surface area (from 0.0427 μm2 to 0.0234 μm2), and initial success rate (from 0.609 to 0.353), indicating a tightening of synaptic transmission with development. Altogether, these results suggest a close correspondence between the number of functionally defined vesicular docking sites and that of clusters of voltage-gated calcium channels.